Implementation of the ward based primary health care outreach teams in the Ekurhuleni health district: a process evaluation - Whyte, Carmen (My University, 2015)
Introduction: One of the aims of the re-engineering of primary health care in South Africa is to strengthen the health system and improve accessibility of health services through ward based outreach teams (WBOTs) comprising of nurses and community health workers. Aim: To evaluate the implementation of WBOTs against national guidelines and identify Community Health Worker (CHW) characteristics that influence adherence to guidelines regarding the referral and follow up of maternal and child health clients. Methodology: This cross-sectional study was conducted during 2013. All 9 WBOTs at the time were included in the study. Data were collected through: a questionnaire survey; key informant interviews and a review of records of pregnant, post-natal women and unimmunized children under five. A process evaluation was conducted to describe inputs (training, team composition, resources, and knowledge); processes (service delivery, referral linkages, support and supervision) and outputs (number of clients referred and followed up). Logistic regression was performed to identify CHW characteristics (Age, education, experience, training, and knowledge) associated with adherence to national guidelines. Results: WBOT had sufficient numbers of CHWs within the team; however lacked sufficient knowledge and resources required to conduct household visits. CHWs adhered to the guidelines regarding the follow up of maternal clients with 85% of CHW having conducted the required number of follow up visits for pregnant and postnatal women. However, only 29% of unimmunized children were appropriately followed up. Challenges identified included: lack of supervision, limited resources, and poor knowledge. There was no statistically significant association between CHW characteristics and adherence to guidelines. Conclusion and recommendations: This study highlights the challenges that need to be addressed around the WBOT implementation. It is recommended that there is improvement in resource availability, CHW supervision, capacity and training to improve the implementation process of future teams. Key words: Ward Based Outreach Teams, Primary Health Care re-engineering, Community Health Worker
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Medicine in the branch of Community Health Johannesburg, November 2015
Keywords: Health Services; Community-Institutional Relations